Flash boys [compact disc, unabridged] : a Wall Street revolt - Lewis, Michael (Michael M.) (Simon & Schuster Audio, 2014)
Michael Lewis returns to the financial world with a new book that gives readers a ringside seat as the biggest story in years prepares to hit Wall Street.